KONSEP PURWARUPA PATOK BATAS WILAYAH MENGGUNAKAN WEMOS D1 DAN METODE TRIANGULASI - Kresno Kresno Aji; Bambang Soedijono Wiria Atmadja; Eko Pramono (Universitas PGRI Yogyakarta, 2019)
This article illustrates on regional boundary stakes, the research that has been carried out so far is the manufacture of regional boundary stakes using GPS and GSM. This research has limitations, because not all regions in Indonesia have a good and stable GSM signal. Regarding this matter, the research on making boundary stakes prototypes was carried out using Wemos D1. The prototype of the boundary stakes does not use GPS or GSM, but uses the dbm / RSSI signal as a monitoring tool. The method used in this study uses a modified Triangulation method, compositions from Vincent Pierlot and Marc Van Droogenbroeck. This calculation method proved to be useful for finding Wemos D1 positions without using GPS and GSM devices. The results of research using the Triangulation calculation method proved successful in finding the position of Wemos D1 close to the actual coordinate position, besides the use of more Access Points in this study proved to be able to produce better accuracy.